Social dislocations caused by college education: actions and perceptions of mediators graduated in Countryside Education of Campo da Transamazônica and Xingu - Alcione Sousa de Meneses; Ramonildes Alves Gomes (Universidade Federal do Norte do Tocantins, 2021)
The present work focuses on individuals with Licentiate degree in Countryside Education of UFPA - Campus of Altamira, regarded as mediating agents who consider themselves participants in peasantry-related actions. The main objective of this study is to analyze, through a qualitative research approach, the historical dimension present in class continuity assumption supported by these mediating groups (referred as Social Movement of Transamazônica), associated with the sense of change they have developed in college thus affecting their mediating scope. The data obtained through techniques of individual and focus groups interviews reveal that incorporating and using certain forms of capital (institutionalized through college education) has contributed to the emergency of mediators, some of them deriving from local leadership positions and others intermediating demands, resources, etc. In both cases, these groups may be building local instances of power, by creating chances of political inclusion or even questioning internally the collective action itself.